The correlation between tonsillectomy and Covid-19 infection - Hameed Wadi, Hani; Amer Hadi Al-Majmaie, Ahmed; Shakir Motib, Anfal (Diyala Journal of Medicine, 2023)
Background: The role of tonsillectomy history on the course of COVID-19 infection has not been determined, including COVID-19 colonization in the tonsillar tissue and reduce the cytokine activity of palatine tonsil tissue and the immune response of humoral with cellular immune. Objective: To determine the effect of tonsillectomy in the development of COVID-19 infection. Patients and Methods: It was collected 150 cases diagnosed with COVID-19 and they admitted to Diyala Hospitals. Data including age, gender, smokers, and symptom status were collected. Results: The total number of the patients who were positive COVID-19 was 150, the 102 (68%) of them were males and 48 (32 %) were females. It was found that the highest incidence rate was noticed among non-smoking patients (114 cases) compare to smokers (36 cases) (p<0.0001). It was appeared a significant difference (p<0.0001) of the symptoms of COVID-19 patients with tonsillectomy relative to the patients without tonsillectomy history. Conclusion: Patients that infected with COVID-19 and they have a history of tonsillectomy have more systemic response including fever, chills and other symptoms compare to the patients without tonsillectomy history.